Innovation in Learning the Art of Tanggai Dance from South Sumatra Using Video Media and Flashcards in Elementary Schools - Ega Krisna Pradita (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Education is responsible for integrating, nurturing, and fostering the development of students' talents and creative abilities. This study examines the role of teachers in fostering children's creativity. This study aims to determine how Flash Cards can foster children's creativity in dance lessons, specifically the Tanggai dance from South Sumatra, in elementary schools. The method used in this study was a literature review through a systematic approach to data analysis. The results of this study indicate that teachers make changes to the learning process using Flash Cards to foster children's dance creativity. Using Wallas' theory, through the stages of preparation, incubation, illumination, and verification, children can become active and creative individuals. Flash Cards represent a teacher's innovation in transforming the learning process. This medium can foster children's creativity and active expression through movement, enabling them to be more active and creative, moving from viewing images to dance movements. It is hoped that the results of this study can serve as reference material or development for further research.